Politics, violence, memory : the new social science of the Holocaust - Kopstein, Jeffrey; Subotic, Jelena; Welch, Susan (Cornell University Press, 2023)
"This book highlights important new social scientific research on the Holocaust and initiates the integration of the Holocaust into mainstream social scientific research in a way that will be useful both for social scientists and historians"--